2008
DOI: 10.1080/08946560801973085
|View full text |Cite
|
Sign up to set email alerts
|

County Government Resources Associated with Dependent-Adult Abuse Investigations in Iowa

Abstract: This study evaluated on a county level the association of Iowa's domestic dependent-adult abuse investigations with the location of adult protective services (APS) offices, rurality, government resources, felony charges and prosecutions, child abuse reports, and census demographics. In 2003, the rate of dependent-adult abuse investigations for Iowa was 0.70 per 1,000 population age 18 and older. Higher rates of child abuse investigations, felony prosecutions, sheriff's annual salary, and lower rates of child a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In previous studies, the county demographics and government characteristics were significantly associated with Adult Protective Services investigations and substantiations. 12 - 15 In this study, prosecution rates associated with these variables were tested and population per square mile were close to statistically significant. These may explain the one county, Polk County, with highest sheriff’s mean salary and densest population had higher prosecution rate than that of the average of all other counties.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In previous studies, the county demographics and government characteristics were significantly associated with Adult Protective Services investigations and substantiations. 12 - 15 In this study, prosecution rates associated with these variables were tested and population per square mile were close to statistically significant. These may explain the one county, Polk County, with highest sheriff’s mean salary and densest population had higher prosecution rate than that of the average of all other counties.…”
Section: Discussionmentioning
confidence: 86%
“…14 Government variable selection was based on earlier research in which higher dependent adult substantiations were significantly associated with higher rates of prosecuted felonies and the county attorney’s and sheriff’s annual salary. 15 …”
Section: Methodsmentioning
confidence: 99%
“…The Daly and Jogerst team found that certain social factors were associated with higher rates of APS substantiation: higher population density, poverty and child abuse, child abuse investigations and substantiations, felony prosecutions, and sheriff's salaries. Increased training for and having specialized APS investigators, as well as separate adult and child abuse investigators also yielded more substantiations (Jogerst & Daly, 2008;Jogerst et al, 2003;Jogerst et al, 2000). Importantly, requiring investigators to hold social work degrees also correlated with higher substantiation rates, as well as having tracking systems for cases (Daly et al, 2005;Jogerst et al, 2004).…”
Section: Substantiation Of Abuse and Neglect Reportsmentioning
confidence: 87%
“…Only three research teams have used APS data to analyze patterns of reported abuse substantiation by APS investigators: Daly and Jogerst and their colleagues (who provided five articles on the subject: Daly, Jogerst, Haigh, Leeney, & Dawson, 2005;Jogerst & Daly, 2008;Jogerst et al, 2003;Jogerst et al, 2004;Jogerst, Dawson, Hartz, Ely, & Schweitzer, 2000), , and Ramsey-Klawsnik, Teaster, Mendiondo, Marcum, and Abner (2008). The Daly and Jogerst team found that certain social factors were associated with higher rates of APS substantiation: higher population density, poverty and child abuse, child abuse investigations and substantiations, felony prosecutions, and sheriff's salaries.…”
Section: Substantiation Of Abuse and Neglect Reportsmentioning
confidence: 96%